Science parks clusters and regional development - Ylinenpää, Håkan (Luleå tekniska universitet, Innovation och Design, 2001)
A Science or Research park is generally regarded as an arena for either developing university - industry co-operation or as an arena for spin-out ideas from university research to ‘take off' during market introduction. To an increasing extent, however, Science Parks are also viewed as measures to promote a favourable regional development. This paper discusses (i) strategies related to the favourable development of Science Parks, and (ii) whether the concept of Science Parks may be used as a tool for regional development Godkänd; 2001; Bibliografisk uppgift: Publicerad i serien Arbetsrapporter, Institutionen för industriell ekonomi och samhällsvetenskap, avd. för industriell organisation, Luleå tekniska universitet, AR 2001:48; 20070207 (keni)